1998
DOI: 10.1002/(sici)1096-9837(199804)23:4<291::aid-esp844>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

The role of biota in the initiation and growth of islands on the floodplain of the Okavango alluvial fan, Botswana

Abstract: A group of islands of varying size on the floodplain of the Okavango alluvial fan, were studied to establish the processes which lead to the initiation and growth of islands. It was found that islands are initiated by the mound-building activities of the termite Macrotermes michaelseni. These termites import fine grained materials to use as a mortar for the construction of epigeal mounds. Their activities create a topographic feature, raised above the level of seasonal flooding, and also change the physical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 22 publications
2
73
0
Order By: Relevance
“…The termite mound structures for the most part had a smaller quantity of quartz, balanced with a higher content of phyllosilicate minerals such as smectite and kaolinite, than the adjacent soil horizons. Our result is in agreement with that of McCarthy et al (1998), who found more concentrated phyllosilicate clays (kaolinite and illite) in the fine earth ( 2 mm) beneath M. michaelseni mounds than in the surrounding soil derived from aeolian sands. We speculate that M. bellicosusʼs preferential selection of fine soil particles caused the apparent changes in clay mineralogy in the mound structures, a decreased abundance of quartz balanced with an increased abundance of smectite and/or kaolinite in the mound structures compared with those in the adjacent near-surface (Ap2) horizons.…”
Section: Discussionsupporting
confidence: 93%
“…The termite mound structures for the most part had a smaller quantity of quartz, balanced with a higher content of phyllosilicate minerals such as smectite and kaolinite, than the adjacent soil horizons. Our result is in agreement with that of McCarthy et al (1998), who found more concentrated phyllosilicate clays (kaolinite and illite) in the fine earth ( 2 mm) beneath M. michaelseni mounds than in the surrounding soil derived from aeolian sands. We speculate that M. bellicosusʼs preferential selection of fine soil particles caused the apparent changes in clay mineralogy in the mound structures, a decreased abundance of quartz balanced with an increased abundance of smectite and/or kaolinite in the mound structures compared with those in the adjacent near-surface (Ap2) horizons.…”
Section: Discussionsupporting
confidence: 93%
“…Fig. 8 shows Model B, which is based on observations by McCarthy and Ellery (1995) and McCarthy et al (1998) of the flood cycle in the Okavango Delta in Botswana, a broadly flat region with fluvial channels and areas of slightly higher ground similar to that suggested for the paleowetlands, but differing in the presence of sand. They noted that silica precipitation was induced from groundwater by evapotranspiration from rooted plants, whereas carbonates precipitated in wetland island soils below minor topographic highs.…”
Section: Depositional Modelsmentioning
confidence: 99%
“…Most theories suggest that these tree island types emerge via similar biological and environmental feedback processes. For example, McCarthy et al (1998) reasoned that tree islands in the Okavango delta of Botswana emerge via nucleation around topographic rises associated with termite mounds. Once established, they increase local transpiration thus altering below-canopy soil chemistry and enabling woody patch expansion.…”
Section: Sidroxylon Reclinatummentioning
confidence: 99%